2005
DOI: 10.33588/rn.4105.2004504
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la calidad de vida en la esclerosis múltiple

Abstract: PACIENTES Y MÉTODOS Se realizó un estudio de tipo descriptivo y transversal con pacientes afectados de EM en nuestra área sanitaria. De un total de 519 pacientes con EM definida por neurólogos, tomando como referencia los criterios diagnósticos de McDonald et al [16]. Incluimos en el estudio a aquellos pacientes, con cualquier forma de evolución, que tuviesen una puntuación en la escala EDSS menor o igual a 9 y que se A STUDY OF THE QUALITY OF LIFE IN CASES OF MULTIPLE SCLEROSIS Summary. Aims. Our objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
2
6
0
4
Order By: Relevance
“…The demographic analysis of this series shows that individuals with MS in Rio de Janeiro have demographic characteristics similar to those described in other regions of Brazil [23][24][25][26][27] and in the rest of the world 2,7,8,10,28,29 . From a clinical perspective, the value of EDSS measured after a mean duration of 8.4 years of the disease indicated mild disability in the majority of cases like Ferreira et al 25 .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The demographic analysis of this series shows that individuals with MS in Rio de Janeiro have demographic characteristics similar to those described in other regions of Brazil [23][24][25][26][27] and in the rest of the world 2,7,8,10,28,29 . From a clinical perspective, the value of EDSS measured after a mean duration of 8.4 years of the disease indicated mild disability in the majority of cases like Ferreira et al 25 .…”
Section: Discussionsupporting
confidence: 59%
“…Mean duration of the disease <10 years and the mild disability found in around two-thirds of cases justifies this result. Studies carried out by Janssens et al 8 and Delgado-Mendilívar et al 2 reported a decrease in the general health and vitality domains in series of patients who also had mild disability.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations